Internet connectivity disruption in Bangladesh (Bangladesh) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Bangladesh. Data sourced from IODA.
Network Disruption Incident ID: BD-2026-0077. Severity: critical. Confidence: 65%